(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2000)
The way in which particular personages and stories from the Koran are transformed to become the foundations of folklore texts is dependent on a variety of factors. Perhaps foremost among these is the specific character of the local socio-cultural environment where they come into being and continue to exist. In this account I will focus on field notes, collected among Bulgarian Sunnite Turks living in North-Eastern Bulgaria and the area of the Central Rhodopes. Another relevant factor is the specific interpretation of the inaccessible Arabic text of the Koran, made by the local imam (hodja) for the people whose spiritual leader he is. A third factor is the interpretation of adapted explanations of religious tenets found in textbooks of Islamic belief, as well as the transformation of these explanations themselves into original sources of folk narrative. A fourth factor, among many others, is the life experience of the individual person and the signs, which that person may or may not accept, of God’s presence in human affairs.